Increasing partner communication and understanding during pregnancy: evaluation of 'The Great Pregnancy Quiz'. (8th August 2021) - Matthey, Stephen; Cibralic, Sara; Leonard, Katrina; Baker, Vanessa
ABSTRACT: Objective: To evaluate a Quiz designed to enhance communication and understanding in expectant parents. Background: A supportive and understanding relationship is associated with better maternal mental health outcomes. Many services therefore advocate that couples should communicate openly with each other, particularly about worries or concerns either have. To facilitate this a quiz (The Great Pregnancy Quiz) was developed and evaluated in this project. Method: English-speaking women (N = 442) and men (N = 146) were recruited from antenatal clinics or classes and were given the 'Great Pregnancy Quiz' to complete at home. Approximately 2–4 weeks (T2) later they participated in either a phone interview, an online survey, or a face-face interview, still during the pregnancy, concerning the impact of the Quiz. Data were available from 90 women and 46 men. Data were analysed using a mixed-methods single group post-test only design. Results: Most women (78 of the 90: 87%) and men (35 of the 46: 76%) reported that the Quiz had positively impacted either their understanding or knowledge of each other. For 30 of the 90 women (33%) and 3 of the 46 men (7%) one or other had implemented some new supportive behaviour due to the Quiz. Qualitative comments highlight the impacts of the Quiz. Conclusion: Most couples who did the Quiz reported positive impacts on their communication and understanding. While the issue of low T2 contact rates may have skewed the results, the benefits associated with the quiz make this resource an inexpensive and easily implemented health promotion strategy.